Role of endoplasmic reticulum stress in cell apoptosis induced by duck hepatitis A virus type 1 infection - Lan, Jingjing; Zhang, Ruihua; Xu, Guige; Yan, Hui; Wang, Jingyu; Shi, Xingxing; Zhu, Yanli; Xie, Zhijing; Jiang, Shijin (Frontiers in Immunology, 2025)
The endoplasmic reticulum (ER), an elaborate cellular organelle that interweaves the cytosol, nucleus, mitochondria and plasma membrane, is essential for cell function and survival. Disruption of ER function can trigger unfolded protein response (UPR), which is activated by ER stress (ERS). In this study, we investigated the role of ERS in cell apoptosis induced by duck hepatitis A virus type 1 (DHAV-1) infection. Our findings revealed that DHAV-1 infection led to the activation of ERS. Specially, the expression of glucose-regulated protein 78 (GRP78) was upregulated, activating two pathways of UPR: the protein kinase R-like ER kinase (PERK) pathway and the inositol-requiring enzyme 1(IRE1) pathway. Consequently, phosphorylation of eukaryotic initiation factor 2 alpha (p-eIF2α) was increased, and transcription factor 4 (ATF4) was up-regulated, resulting in the induction of the apoptotic C/EBP homologous protein (CHOP). DHAV-1-infected cells exhibited various apoptotic phenotypes, including growth arrest, induction of the DNA damage-inducible protein 34 (GADD34), activation of caspase-3, and suppression of antiapoptotic protein B cell lymphoma-2 (Bcl-2). Importantly, inhibition of PERK or protein kinase R (PKR) activity suppressed CHOP activation and DHAV-1 replication, indicating that the PERK/PKR-eIF2α pathway played a crucial role in ERS-induced apoptosis. Collectively, our study provides novel insights into the mechanism of DHAV-1-induced apoptosis and reveals a potential defense mechanism against DHAV-1 replication.